Efecto de la adición de carbonato de bismuto en óxido de zirconio en el proceso de producción de hidrógeno vía fotocatalítica - Castillo Rodríguez, Julio César (Universidad Autónoma Metropolitana, 2022)
The present investigation describes the synthesis, characterization and photocatalytic evaluation of the composite materials ZrO2-Bi2O2(CO3) which were synthesized by the chemical co-precipitation method. The solids were prepared by modifying the content of Bi2O2(CO3), obtaining samples at 0.5, 1 and 2% mol, in order to determine the influence of the percentage of Bi2O2(CO3) in ZrO2 on the production of H2 via photocatalytic process. The same mechanism of synthesis, characterization and photocatalytic evaluation of the reference materials ZrO2 and Bi2O2(CO3) was carried out to compare their activity with that of the composite materials. The materials were characterized in order to study their structural, textural and optical properties. In this sense, the solids were analyzed by X-ray diffraction, diffuse reflectance UV-Vis spectroscopy, infrared spectroscopy, scanning electron microscopy, high resolution transmission electron microscopy, photoluminescence spectroscopy, N2 physisorption, and X Ray photoelectron spectroscopy. The evaluation of the photocatalytic activity of the materials was carried out in the production of H2 under UV light irradiation. The results showed that ZrO2 with the addition of Bi2O2(CO3) significantly improves the photocatalytic behavior compared to the reference materials.